A fuzzy micro-climate controller for small indoor aeroponics systems - Bambang Dwi Argo; Yusuf Hendrawan; Ubaidillah Ubaidillah (Universitas Ahmad Dahlan, 2019)
The Indonesian agricultural sector faces challenges producing affordably priced food using sustainable practices. A soilless cultural practice, such as indoor aeroponics, is a compelling alternative to conventional agriculture. The objective of the present study was to develop a system for micro-climate management in a pilot-scale indoor aeroponics system. For this purpose, three fuzzy logic controllers were developed and evaluated to maintain plant chamber parameters (temperature, relative humidity, and light intensity) at desired set points controlled by embedded system controls designed using BASCOM-AVR software. The results showed that the fuzzy controllers provided excellent responses and experienced relatively low errors in all controlled parameters. All parameters changes followed the set point very smoothly and responded accordingly.The averaged percent of working times in which temperature, relative humidity, and light intensity were maintained within less than ±1°C, ±5%, and ±30 lux from the set points were found to be 88.43%, 95.91%, and 85.51%, respectively.